Protection of the Rights of the Child Under the Auspices of the Hague Conference on Private Law - Tomczewska, Agnieszka (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract:In today’s times of increasing globalisation and easy movement of people, the mobility of families between countries is very common. It is very important to secure the rights of the child as fully as possible in such situations. The most well-known convention constituting a substantive legal basis for a wide range of children’s rights is the 1989 UN Convention on the Rights of the Child. However, this Convention alone would not be sufficient to guarantee the rights provided for therein, as well as to implement the principle of the best interests of the child in cross-border situations. The lack of international solutions common to states would result in the fact that in cross-border cases, different legal systems of individual countries in which the child resides or with which he/she has a certain relationship would apply. The lack of regulation in this area would, therefore, cause legal uncertainty regarding the child’s situation, expose him/her to the lack of necessary legal protection, and could lead to a violation of his/her rights. This state of affairs contributed to the creation of an international system of child protection under the Hague Conventions within the framework of the Hague Conference on Private Law. The most well-known and widely used conventions are the 1996 Convention and the 1980 Convention. These conventions harmonise the conflict-of-law and jurisdictional rules in cases involving children at the international level and, by creating a special return mechanism, address the situation of unlawful transfer of a child from one country to another without the consent of the parent in whose custody the child was also staying. Thanks to such solutions, the continuity of child protection and stabilisation of the child’s legal situation is ensured. On the other hand, countries involved in the child’s case may cooperate directly with each other to guarantee the child’s legal protection and safety. It is worth noting that cross-border situations in which the provisions of the Convention may apply can be very diverse. They may concern the ordinary movement of a child with his/her family, as well as cases of much greater dynamics and a high emotional load related to unlawful child abduction. The Conventions also regulate the situation of children who are left unaccompanied and do not have their habitual residence in the countries. This article aims to show how the legal solutions contained in the two Hague Conventions of 1996 and 1980 contribute to the protection of the rights of the child and the best interests of the child in cross-border situations. Keywords: 1996 Hague Convention, 1980 Hague Convention, conflict of law rules, applicable law, cooperation between central authorities, habitual residence, right of access to the child’s parents